Indonesia Pengembangan Sistem Monitoring Pengumpulan Soal Ujian Berbasis Website Untuk Modul Ketua Program Studi Dengan Metode Waterfall - Aulia Ferina Sendhitasari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Telkom University, is one of the many private universities in Indonesia. Telkom University was established on August 14, 2013. Telkom University consists of 7 Faculties, one of which is the Faculty of Industrial Engineering. The address of the Faculty of Industrial Engineering is located at Jl Telekomunikasi Terusan Buah Batu No. 1, Gedung Karang 40257, Bandung, Indonesia. This faculty has four study programs, namely S1 Information Systems, S1 Industrial Engineering, S2 Industrial Engineering and Logistics Engineering. This research is a research in the development of a website-based question collection monitoring system for the study of the module head program with the waterfall method. In the development of the application for monitoring the collection of exam questions, the waterfall method will be applied, in which the application is carried out from the stages of planning, analysis, design, implementation and use and application with object modeling which is between admin and interacts with each other's information. From the results of the application of the waterfall method on the development of test collection applications with oriented modeling, it produces convenience and conciseness in exam activities and more effective and efficient sales data processing. Keywords : System development, waterfall.